2019
DOI: 10.1039/c8sc04344b
|View full text |Cite
|
Sign up to set email alerts
|

Cathodized copper porphyrin metal–organic framework nanosheets for selective formate and acetate production from CO2 electroreduction

Abstract: Highly selective and effective formate and acetate production from CO2 electroreduction on cathodized metal–organic framework nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(145 citation statements)
references
References 57 publications
2
143
0
Order By: Relevance
“…Electrochemical reduction of CO 2 to valuable chemical feedstocks or fuels using renewable electricity contributes to closing the artificial carbon cycle. [ 1 ] The sophisticated multi‐electron transfer process leads to a multitude of possible CO 2 reduction products ranging from C 1 (CH 4 , [ 2 ] CO, [ 3 ] HCOOH [ 4 ] ) to C 2+ (C 2 H 5 OH, [ 5 ] CH 3 COOH, [ 6 ] C 2 H 4 , [ 7a,b ] C 2 H 6 , [ 7c ] and CH 3 CH 2 CH 2 OH [ 5 ] ) productions, especially for copper‐based catalysts. [ 7d ] Even though the C 2+ products possess higher industrial values, [ 8 ] CO 2 electroreduction to C 2+ products in industrial level remains a substantial challenge due to its low selectivity and sluggish reaction pathway, eventually resulting in high production cost.…”
Section: Figurementioning
confidence: 99%
“…Electrochemical reduction of CO 2 to valuable chemical feedstocks or fuels using renewable electricity contributes to closing the artificial carbon cycle. [ 1 ] The sophisticated multi‐electron transfer process leads to a multitude of possible CO 2 reduction products ranging from C 1 (CH 4 , [ 2 ] CO, [ 3 ] HCOOH [ 4 ] ) to C 2+ (C 2 H 5 OH, [ 5 ] CH 3 COOH, [ 6 ] C 2 H 4 , [ 7a,b ] C 2 H 6 , [ 7c ] and CH 3 CH 2 CH 2 OH [ 5 ] ) productions, especially for copper‐based catalysts. [ 7d ] Even though the C 2+ products possess higher industrial values, [ 8 ] CO 2 electroreduction to C 2+ products in industrial level remains a substantial challenge due to its low selectivity and sluggish reaction pathway, eventually resulting in high production cost.…”
Section: Figurementioning
confidence: 99%
“…Sun et al [11] have used density functional theory to propose a 2D MOF-based on molybdenum for NRR. With highly ordered structure and exposed metal active sites, the Mo-based MOF could exhibit an excellent catalytic performance for the conversion of N 2 into NH 3 at room temperature with a very low overpotential of 0.18 V. Further, Wu et al [20] have demonstrated copper porphyrin metal-organic framework nanosheets as highly selective and efficient electrocatalysts for the electroreduction of CO 2 to formate and acetate (CO 2 RR), with a maximum faradaic efficiency of 61.5% and 12.3% respectively. The authors attribute the efficiency of the electrocatalyst to its flat and high-aspect-ratio which promoted electron transfer and reduced the diffusion kinetic barrier, confirming that MOF downsizing is a feasible method for the further improvement of 2D nanosheet conductivity.…”
Section: Energy-related Applications Of 2d Metal-organic Frameworkmentioning
confidence: 99%
“… Electron micrographs of MOFs that have been used as catalyst supports: a) SEM and b) TEM images of Cu 2 (CuTCPP) nanosheets . c) Top‐down and d) cross‐sectional SEM images of a Cu‐SIM NU‐1000 thin film .…”
Section: Mof‐related Catalysts For Co2ermentioning
confidence: 99%
“…Wu et al. used porphyrinic MOF nanosheets to promote the CO 2 ER . The Cu 2 (CuTCPP) nanosheets were cathodized onto FTO glass and exhibited significant activity for the production of formate, with a FE of 68.4 % at −1.55 V (vs. Ag/Ag + ).…”
Section: Mof‐related Catalysts For Co2ermentioning
confidence: 99%